2011
DOI: 10.1037/a0020333
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of time estimation following moderate to severe traumatic brain injury.

Abstract: Objective Accurate time estimation abilities are thought to play an important role in efficient performance of many daily activities. This study investigated the role of episodic memory in the recovery of time estimation abilities following moderate to severe traumatic brain injury (TBI). Method Using a prospective verbal time estimation paradigm, TBI participants were tested in the early phase of recovery from TBI and then again approximately one year later. Verbal time estimations were made for filled inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(36 citation statements)
references
References 67 publications
(112 reference statements)
3
32
0
1
Order By: Relevance
“…In fact, temporal dysfunctions were observed when the temporal intervals exceeded the working memory span (Schmitter-Edgecombe and Rueda, 2008; Anderson and Schmitter-Edgecombe, 2011) or when the tasks employed required high cognitive functions to be performed (Mioni et al, 2013a,b). The consistent higher temporal variability observed is a sign of impaired frontally mediated cognitive functions that affect temporal representation.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, temporal dysfunctions were observed when the temporal intervals exceeded the working memory span (Schmitter-Edgecombe and Rueda, 2008; Anderson and Schmitter-Edgecombe, 2011) or when the tasks employed required high cognitive functions to be performed (Mioni et al, 2013a,b). The consistent higher temporal variability observed is a sign of impaired frontally mediated cognitive functions that affect temporal representation.…”
Section: Discussionmentioning
confidence: 99%
“…This may be specifically relevant to brain injury as dopamine release is severely attenuated after focal experimental injury [17], and dopamine transporters and receptor levels are altered in patients with TBI [18, 19]. While relatively few studies have examined timing in TBI patients, the collective data are suggestive of increased variability in timing abilities, and very much task dependent [2022], particularly when considering injury severity and recovery [23]. To better understand changes in timing due to TBI, and its relation to impulsivity, animal models are needed to parse specific contributing variables.…”
Section: Introductionmentioning
confidence: 99%
“…Considering the underestimation pattern observed in neglect (Calabria et al ., ; Danckert et al ., ; Oliveri et al ., , ), it has been previously reported that right brain‐damaged patients without neglect also tend to underestimate durations, while left brain‐damaged patients are relatively spared in duration tasks (Harrington et al ., ; Koch, Oliveri, Carlesimo, & Caltagirone, ; Magnani et al ., ). Moreover, underestimation of durations has been observed in Parkinson's disease (Malapani, Deweer, & Gibbon, ), attentional/hyperactivity deficit disorder (Levin et al ., ), schizophrenia (Lee et al ., ), traumatic brain injury (Anderson & Schmitter‐Edgecombe, ) or patients with frontal or cerebellar lesions (Casini & Ivry, ; Gooch, Wiener, Wencil, & Coslett, ). This lack of specificity goes against the claim that neglect causes a specific underestimation pattern in duration estimation due to impaired attention processes.…”
Section: Discussionmentioning
confidence: 99%